Chemical constituents, antioxidant and antimicrobial activities of Pterygota alata (Roxb.) leaves extracts grown in Egypt - Maha E. Omran; Azza A. Shafei; Sally E. Abdel-Rahman (Novel Research in Microbiology Journal)
Overproduction of reactive species and microbial resistance to the existent antibiotics are still great health challenges. The current study aimed to evaluate the antioxidant and antimicrobial activities of Pterygota alata leaves extracts, in addition to isolation and identification of their chemical constituents. In vitro antioxidant activity was explored using 2,2'-diphenyl-1-picrylhydrazyl radical scavenging assay (DPPH), whereas the in vitro antimicrobial activity was evaluated using the disc agar plate method. Chemical constituents of the leaves extracts were isolated through column chromatography, and then identified using 1H, 13C-NMR and IR spectroscopic tools. In the DPPH assay; the half maximal inhibitory concentration (IC50) value of the total extract was 72.4 ± 1.4 µg/ ml, relative to 11.2 ± 0.6 µg/ ml of the standard ascorbic acid. On the other hand; the antimicrobial results revealed that the ethyl acetate extract showed the strongest inhibitory potential against most of the tested microbes with inhibition zones of 16.8- 22.8 mm, followed by petroleum ether with inhibition zones between 13.4- 19.6 mm, and n-BuOH with inhibition zones ranging from 14.9-19.3 mm. These results were compared with the standard antibiotics such as; Amphatricin β, Ampicillin, and Gentamycin. Furthermore; chromatographic isolation of the different solvents extracts resulted in the isolation of five phytoconstituents, their chemical structures were assigned as; β-sitosterol (1), apigenin-7-β-D-glycoside (2), gallic acid (3), luteolin-7-β-D-glucoside (4), and 4'- methoxy myricetin-3-β-D-glucoside (5). Current findings suggested that leaf extracts of P. alata could be used for the development of natural drugs; to treat microbial infections and reactive oxygen species (ROS) associated disorders.